Sosialisasi Teknik Penyambungan Papan Kulit ke Gading dan Lunas pada Kapal Kayu dengan Rangka Konstruksi Baja - Sitepu, Ganding; Ardianti, Andi; Firmansyah, Muhammad Rizal; ., Misliah; Djafar, Wihdat; Djalante, A. H.; Bochary, Lukman; Clauthaldi, F. R.; Matemmu, Jeferi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
The construction of wooden boats for fishermen in South Sulawesi is starting to find it difficult to get high-quality wood, especially for boat hulls. An alternative to wood as a wooden ship hull is steel. The problem of joining or fastening planking boards made of wood with a steel frame is not fully understood by the wooden boat craftsmen in Galesong. For this reason, this activity aims to socialize the binding of planking boards with wooden ship steel frames to the "Patorani" craftsman group in Galesong District, Takalar Regency. The activity was carried out using the lecture method (socialization) and a simple demonstration using a wooden ship model. The results of the activity showed that the members of the craftsman group were very enthusiastic about participating in the activity and hoped that steel could replace wood as a ship construction material. Prior to the activity, almost none of the craftsmen group members had seen and knew that steel could be used as a ship's hull, and at the end of the socialization, they believed that steel could be a substitute for wood as a wooden ship's hull so that the construction and production of wooden ships would continue. Furthermore, it is also seen that members of the craftsman group can understand the technique of installing or fastening planking boards to steel frames.